Collusive Tax Evasion by Employers and Employees: Evidence from a Randomized Field Experiment in Norway - Marie Bjørneby; Annette Alstadsæter; Kjetil Telle (Center for Economic Studies and ifo Institute (CESifo), 2018)
Third-party reporting and employers' tax withholding are powerful compliance mechanisms, as long as the employer and employee do not collude to evade. Using data from randomly assigned on-site audits among 2,462 Norwegian firms, we provide evidence of collusive tax evasion. We find that firms assigned to be audited increased their subsequent wage reporting on behalf of their employees by 18 percent relative to firms assigned to the control group. The effect is more pronounced among small firms with few employees. Our results document the limitations of third-party reporting, but also that these limitations can be counteracted by relatively inexpensive on-site audits.
Keywords: E26; H26; H32; 330; collaborative tax evasion; collusive tax evasion; random audits; undeclared work; third-party reporting